Optimizing preparedness and response for circulating vaccine derived poliovirus (cVDPV) outbreaks in the Eastern Mediterranean Region with a particular focus on cVDPV2 - Haddad, Nadine; Jarour, Najwa; Shukla, Hemant; Tsega, Asnakew; Akbar, Irfan; Mahmoud Qasim Shahrour, Ghada; Sekhar Kar, Subhranshu; Al Nsour, Mohannad; Gunaid, Magid; Khader, Yousef (Frontiers in Public Health, 2025)
Efforts to achieve polio eradication in the Eastern Mediterranean Region (EMR) are confronted by several barriers stemming from the volatile security and political instability in several countries, to social contextual challenges such as inaccessible and mobile/displaced population, to logistic issues hindering optimal implementation of immunization and surveillance interventions. To further understand these challenges and emphasize improvement areas, the Eighth Regional Conference of the Eastern Mediterranean Public Health Network (EMPHNET), that was held in Amman, Jordan from September 15–18, 2023, featured a workshop focused on scaling up outbreak preparedness and response efforts. A variety of relevant experts and audiences from outbreak and at-risk countries in the EMR described their capacities, best practices and lessons learned from their national experiences. Overall recommendations were outlined, aiming to enhance preparedness and response to cVDPV outbreak in target countries and in the region overall.